A quantum chemistry description of carbon monoxide and water absorbates on single-crystal rhodium and platinum clusters - Paredes Olivera, P. (1994)
Extended Hückel molecular-orbital calculations of CO and HO adsorbed ensembles on single-crystal Pt and Rh clusters are presented. The energy ranges related to the stability of adsorbed ensembles of the type (Me)N(CO)n(OH)m, where Me stands for Rh(100), Rh(111), Pt(100) and Pt(111), were calculated for various coordination geometries and applied potential conditions. A stability inversion potential was found for each ensemble. A correlation was obtained between the stability inversion potentials resulting from the different adsorbed ensembles and the potentials of the current peaks related to the voltammetric oxidation of CO adsorbates on Pt and Rh resulting from comparable potential perturbation conditions.